(untitled) (Innovaciones Educativas, 2025)
The degree programs of Microbiology and Clinical Chemistry (MQC) and Diploma in Laboratory Assistant (DAL) of the University of Costa Rica (UCR) present a high demand, which deserves having criteria that allow a valid student selection, with equity and excellence. Therefore, using structural equation models (SEM) it is aimed to generate evidence regarding predictive validity of three tests that assess different constructs: a) fine motor skills (DM), b) fluid intelligence (FLUID), and c) working memory (MEMO). The estimated correlation between response time (TR) and MEMO was high and negative, consistent with what is proposed by the theory of executive functions. MEMO and TR relevantly predict FLUID and DM. MEMO presents direct and strong relationships with both constructs endogenous in Chemistry and Biology. TR exhibits a relationship with FLUID and DM in both subjects. For both subjects, the relationship between TR and FLUID is inverse. The relationship between TR and DM is positive and large. Differences between the estimated models for both subjects are found for the relationships that predict performance in Biology or Chemistry, with MEMO being a significant predictor for both. The DM did not show a significant predictive power. FLUID show relationship with Chemistry, but practically non-existent with Biology. These results provide evidence in favor of using tests that assess MEMO and FLUID for student selection in MQC and DAL. No evidence was generated about the relevance of DM as predictor of university academic performance.